(untitled) (Historia, 2021)
Scarecrow Press are to be congratulated for bringing out so quickly an affordable paperback edition of this volume, which will surely become a standard work of reference, a welcome and reliable companion for scholars and students alike who are working on the Anglo-Boer War. The book is a superb piece of research, scholarship, and clearly the product of many years of careful labour, reflection, and precise exposition. Embellished with maps and a chronology, it has a useful introduction and overview of the origins and course of the war, and contains over 600 cross-referenced entries, covering nearly every conceivable facet of significance in the war. The bibliography, beginning with a scholarly six-page review essay, spans 58 pages and must be the most up-to-date bibliographic source available.